2019
DOI: 10.1177/1757913919826599
|View full text |Cite
|
Sign up to set email alerts
|

Arts for the Blues – a new creative psychological therapy for depression: a pilot workshop report

Abstract: Art s fo r t h e Blu e s -a n e w c r e a tiv e p sy c h olo gi c al t h e r a p y fo r d e p r e s sio n: a pilo t w o r k s h o p r e p o r t H a sl a m , S, P a r s o n s, AS, O mylin s k a-T h u r s t o n, J, N air, K, H a rlow, J, Le wi s, J, Th u r s t o n, SD, G riffin, J, D u b r o w-M a r s h all, LJ a n d Ka r k o u, V h t t p:// dx. d oi.o r g/ 1 0. 1 1 7 7/ 1 7 5 7 9 1 3 9 1 9 8 2 6 5 9 9 Ti t l e Art s fo r t h e Blu e s -a n e w c r e a tiv e p s yc h olo gic al t h e r a p y fo r d e p r e s sio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…These studies confirmed the impact of several common factors of change in psychotherapy beginning with the therapeutic alliance (Heynen et al, 2017 ). Their orientations differ in that some work in the here and now (Flanagan, 2004 ; Parsons et al, 2020 ), while others focus on past events (Parsons et al, 2020 ), creative arts therapists tailor the therapeutic goals to meet individual and group needs, facilitate fundamental relational skills and features, and promote supportive relationships (Heynen et al, 2017 ; Kalaf and Plante, 2019 ; Parsons et al, 2020 ). CATs take place in a liberating environment characterized by trust and safety (Chiang et al, 2019 ), in which clients can experience a sense of agency and skill with regard to processing and communicating emotions and forming connections with others (Dunphy et al, 2019 ; Kalaf and Plante, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies confirmed the impact of several common factors of change in psychotherapy beginning with the therapeutic alliance (Heynen et al, 2017 ). Their orientations differ in that some work in the here and now (Flanagan, 2004 ; Parsons et al, 2020 ), while others focus on past events (Parsons et al, 2020 ), creative arts therapists tailor the therapeutic goals to meet individual and group needs, facilitate fundamental relational skills and features, and promote supportive relationships (Heynen et al, 2017 ; Kalaf and Plante, 2019 ; Parsons et al, 2020 ). CATs take place in a liberating environment characterized by trust and safety (Chiang et al, 2019 ), in which clients can experience a sense of agency and skill with regard to processing and communicating emotions and forming connections with others (Dunphy et al, 2019 ; Kalaf and Plante, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies revealed that the CATs actively engage (Parsons et al, 2020 ) participants in artistic therapeutic activity and offer multiple options for verbal and non-verbal expression through symbolism and metaphor (Flanagan, 2004 ; Schiltz, 2014 ; Chiang et al, 2019 ; Dunphy et al, 2019 ). The CATs facilitate concretization , to make visible internal conflicts , which enables perspective-taking (Schiltz, 2014 ; Kalaf and Plante, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In-depth study of the manuals of the different types of DMT practice used can result in further refinement of what we think is currently responsible for the significant effects of DMT on reducing depression. A new project called “Arts for the Blues” (Haslam et al, 2019; Karkou et al, 2019; Parsons et al, in press) may offer relevant support in this direction for DMT as well as the other arts therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the therapeutic model (Figure 1), each session was focused on a specific topic and therapeutic goals, based on existing evidence of previous arts therapies interventions (Hilliard, 2001;Koshland et al, 2004;Karkou and Sanderson, 2006;Choi et al, 2008;Karkou, 2010). There were also strong influences from the project ' Arts for the Blues, ' a study that supported the development of an evidence-based creative intervention for adults (Haslam et al, 2019;Parsons et al, 2019). Each session has been described thoroughly in the study protocol (Moula et al, 2019).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The therapeutic protocol was also developed through a synthesis of previous interventions that had been successfully implemented and assessed by children themselves. It was also informed by other evidence-based arts therapies protocols (Haslam et al, 2019;Parsons et al, 2019). The detailed description of the therapeutic protocol (Moula et al, 2019), and the process evaluation from the perspectives of children, researchers and arts therapists in a forthcoming publication (Moula et al, in preparation), are expected to make this intervention replicable in future studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%